2020
DOI: 10.3389/fmed.2020.543290
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Health Utility Estimates in Chronic Spontaneous Urticaria

Abstract: Background: Chronic spontaneous urticaria (CSU) is a common recurrent skin disease that adversely affect patient's quality of life condition to treat. Economic evaluations of health care often include patient preferences for health outcomes using utilities.Objectives: The study aimed to determine pooled estimates of utility-based quality of life in patients with CSU.Methods: We conducted a systematic review, meta-analysis, and meta-regression of peer-reviewed articles and conference papers that published from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 45 publications
0
8
0
3
Order By: Relevance
“…Furthermore, the terminology used to describe the QA process varied considerably among the SLRs. Terms such as quality appraisal or assessment [ 9 , 23 , 24 , 48 , 49 , 51 , 53 , 55 , 57 60 , 73 78 ], critical appraisal [ 47 ], risk of bias assessment [ 25 , 62 , 63 , 72 , 79 82 ], relevancy and quality assessment [ 52 , 56 ], assessment of quality and data appropriateness [ 50 ], methodological quality assessment [ 26 , 27 , 46 , 54 , 61 , 69 ], reporting quality [ 71 , 83 ] credibility checks and methodological review [ 70 ] were used loosely and interchangeably. One study [ 84 ] mentioned three terms, RoB, methodological quality and reporting quality, in their description of the QA process.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the terminology used to describe the QA process varied considerably among the SLRs. Terms such as quality appraisal or assessment [ 9 , 23 , 24 , 48 , 49 , 51 , 53 , 55 , 57 60 , 73 78 ], critical appraisal [ 47 ], risk of bias assessment [ 25 , 62 , 63 , 72 , 79 82 ], relevancy and quality assessment [ 52 , 56 ], assessment of quality and data appropriateness [ 50 ], methodological quality assessment [ 26 , 27 , 46 , 54 , 61 , 69 ], reporting quality [ 71 , 83 ] credibility checks and methodological review [ 70 ] were used loosely and interchangeably. One study [ 84 ] mentioned three terms, RoB, methodological quality and reporting quality, in their description of the QA process.…”
Section: Resultsmentioning
confidence: 99%
“…Although this review included a large number of cost studies by proportion, previously conducted reviews primarily considered economic evaluations such as CEAs and CUAs and therefore reported a high proportion of CEAs and CUAs and studies involving model-based analyses [ 29 , 30 , 38 – 40 ]. For those reviews, 62% to 100% of studies included were CEAs or CUAs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a database search, references cited in each of the included studies and relevant (but not included) systematic reviews were manually searched to identify any additional relevant studies, as recommended by the CRD and Cochrane guidelines [ 29 , 30 ]. A hand search of select academic, industry, and medical society proceedings from 2018 to 2020 was also conducted to identify any recent publications that may not have been published yet, including those from the International Society for Pharmacoeconomics and Outcomes Research (ISPOR), the European Association of Hospital Pharmacists, and the Society for Investigative Dermatology.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stull et al 24 in Italy found a profound socioeconomic burden by chronic urticaria and treatment of chronic urticaria lead to better work productivity. Many authors reported the social strain facing CU patients in their life and work which expressed in different psychological problems like anxiety and stress that lead to declination of health related QoL and sometimes to treatment non-compliance and refractory urticaria cases [32][33][34] . The current study showed that mean score of DLQI was significantly higher among CU patients were visiting more than two doctors (p=0.01).…”
Section: Discussionmentioning
confidence: 99%